Predictive accuracy of elevated mitotic rate on lymph node positivity and recurrence in thin melanomas - Ly, Catherine L.; Blaha, Ondrej; Wei, Wei; Galan, Anjela; Kluger, Harriet; Ariyan, Stephan; Olino, Kelly; Clune, James E. (Frontiers in Oncology, 2023)
Background Mitotic rate (MR) is considered an important prognostic factor for melanoma but is not currently used for staging because its nuanced effect is not yet well-delineated. We sought to determine if T category-specific MR is predictive of sentinel lymph node (SLN) positivity, recurrence, and melanoma-specific mortality (MSM). Methods A retrospective review of patients with primary cutaneous melanoma from 1994 to 2020 at a single academic center was performed. Patient demographics and tumor characteristics were recorded. MR was considered elevated for each AJCC8-defined T category if it was ≥2 mitoses/mm2 for T1, ≥4 mitoses/mm2 for T2, ≥6 mitoses/mm2 for T3, or ≥7 mitoses/mm2 for T4. Statistical analysis was performed to assess the predictive accuracy of MR on selected outcomes while controlling for ulceration. Results Data from 2,984 patients with complete records were analyzed. Along with Breslow thickness and ulceration, elevated MR was associated with higher risk of MSM (HR 1.816, P=0.0001). There was no difference among patients with ulcerated T1 or T2 tumors regardless of MR, but those with non-ulcerated T1 or T2 tumors and elevated MR were more likely to have positive SLNs (P<0.0001 and P=0.0043, respectively) and recurrence (P=0.0007 and P=0.0004, respectively) compared to counterparts with low MR. There were no notable differences for T3 or T4 tumors based on MR. Conclusions Elevated MR is associated with SLN positivity and recurrence in thin melanomas, independent of ulceration. SLN biopsy should therefore be strongly considered for patients with non-ulcerated lesions <0.8 mm thick if the MR is ≥2 mitoses/mm2.